Is stress response a new link between adipose tissue and atherogenesis? The role of HSPs/HSF1. - Akoumianakis, I; Antoniades, C (Oxford University Press, 2016)
The role of lipids in atherogenesis is well established; sub-endothelial deposition of oxidised low density lipoprotein (ox-LDL) initiates atherosclerotic plaque formation. Circulating cholesterol is regulated by its dietary intake and endogenous synthesis on one hand, and its elimination from the circulation via LDL-receptors/excretion in the bile on the other hand.2 Various lipid-lowering therapies targeting these regulatory mechanisms are used in patients with dyslipidaemias, significant impacting cardiovascular risk. However, the residual risk after applying existing lipid-lowering strategies highlights the complexity of lipid metabolism and the necessity for broader understanding of the links between lipids and the cardiovascular system.